Programmed cell death 1 genetic variant and liver damage in nonalcoholic fatty liver disease. (March 2023) - Pipitone, R.M.; Malvestiti, F.; Pennisi, G.; Jamialahmadi, O.; Dongiovanni, P.; Bertolazzi, G.; Pihlajamäki, J.; Yki-Järvinen, H.; Vespasiani-Gentilucci, U.; Tavaglione, F.; Maurotti, S.; Bianco, C.; et al.
Abstract : Background and Aims: Programmed cell death 1/programmed cell death-ligand 1 (PD-1/PDL-1) axis has been reported to modulate liver inflammation and progression to hepatocellular carcinoma (HCC) in patients with nonalcoholic fatty liver disease (NAFLD). Here, we examined whether the PDCD1 variation associates with NAFLD severity in individuals with liver biopsy. Methods: We examined the impact of PDCD1 gene variants on HCC, as robust severe liver disease phenotype in UK Biobank participants. The strongest genetic association with the rs13023138 G>C variation was subsequently tested for association with liver damage in 2, 889 individuals who underwent liver biopsy for suspected nonalcoholic steatohepatitis (NASH). Hepatic transcriptome was examined by RNASeq in a subset of NAFLD individuals (n=121). Transcriptomic and deconvolution analyses were performed to identify biological pathways modulated by the risk allele. Results: The rs13023138 C>G showed the most robust association with HCC in UK Biobank (P = 5.28E-4, OR=1.32, 95% CI [1.1, 1.5]) . In the liver biopsy cohort, rs13023138 G allele was independently associated with severe steatosis (OR 1.17, 95%C.I. 1.02-1.34; p=0.01), NASH (OR 1.22, 95%C.I. 1.09-1.37; p<0.001) and advanced fibrosis (OR 1.26, 95%C.I. 1.06-1.50; p=0.07). At deconvolution analysis, rs13023138 G>C allele was linked to higher hepatic representation of M1 macrophages, paralleled by upregulation of pathways related to inflammation and higher expression of CXCR6. Conclusions: The PDCD1 rs13023138 G allele was associated with HCC development in general population and with liver disease severity in patients at high risk of NASH.